Human muscle in gene edited pigs for treatment of volumetric muscle loss - Greising, Sarah M.; Weiner, Joshua I.; Garry, Daniel J.; Sachs, David H.; Garry, Mary G. (Frontiers in Genetics, 2022)
Focusing on complex extremity trauma and volumetric muscle loss (VML) injuries, this review highlights: i) the current pathophysiologic limitations of the injury sequela; ii) the gene editing strategy of the pig as a model that provides a novel treatment approach; iii) the notion that human skeletal muscle derived from gene edited, humanized pigs provides a groundbreaking treatment option; and iv) the impact of this technologic platform and how it will advance to far more multifaceted applications. This review seeks to shed insights on a novel treatment option using gene edited pigs as a platform which is necessary to overcome the clinical challenges and limitations in the field.